Analisis Persepsi Kemampuan Mahasiswa dengan Asesmen Mandiri dalam Pembelajaran Praktik Kerja Profesi Apoteker (PKPA) di Instalasi Farmasi RSUD Dr. Saiful Anwar - Badriyah, Rani Nur; Puspitasari , Vicky; Widya, Reta Anggraeni (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Pharmacist Professional Work Practice (PKPA) provides a learning process for students to gain basic skills in pharmaceutical services. Student perceptions are important to be involved in the development of the PKPA curriculum at the Dr. Saiful Anwar Hospital Pharmacy Department. The purpose of the study was to determine the basic abilities of students in pharmaceutical services during the PKPA process. Perceptions were assessed by self-assessment in the form of a questionnaire containing 7 questions, namely the ability to reconcile drugs, need for drug, selection of drug, analyze Drug Related Problems (DRP), provision of drug product, medicines information and patient education, and Monitoring Drug Therapy (PTO) before starting PKPA (Pre) and after PKPA ended (Post) in 76 students. Students' perceptions of self-assessment provide results in the category of exceeding expectations (index 86.2%), but several abilities are the top priority for improvement, namely need for drug, medicines information and patient education. Based on this, it can be concluded that students have the perception of having overall pharmaceutical service skills but further assessment needs to be done to test the suitability of perceptions with the abilities possessed by students.